Catalogue. - Brun, Jeanne; Tibloux, Emmanuel (Saint-Etienne : Musée d'Art Moderne de Saint-Etienne, 2011)
Achour, Boris ; Arnaud, Pierre-Olivier ; Baldessari, John ; Becher, Bernd & Hilla ; Bublex, Alain ; Burgin, Victor ; Cazal, Philippe ; Chaton, Anne-James ; Closky, Claude ; Creed, Martin ; Demand, Thomas ; Duchamp, Marcel ; Feldmann, Hans-Peter ; Graham, Dan ; Kosuth, Joseph ; Labelle-Rojoux, Arnaud ; Lebel, Jean-Jacques ; Les ready-made appartiennent à tout le monde ; Levé, Édouard ; Mréjen, Valérie ; Polke, Sigmar ; Prévieux, Julien ; Rehberger, Tobias ; Ruscha, Ed ; Starling, Simon ; Tièche, Ambroise ; Veilhan, Xavier ; Zarka, Raphaël
Frans
Catalogue. Saint-Étienne. Musée d'Art Moderne de Saint-Etienne Métropole. 13.05.2011 - 19.09.2011
boek